The Agrifood Market: Essence and Principles of the Organization - Melnikov, Alexander Borisovich; Mikhaylushkin, Pavel Valeryevich; Alieva, Alina Rafaelyevna; Bershitskiy, Yuriy Iosifovich; Tolmachev, Aleksey Vasilevich (International Review of Management and Marketing, 2016)
One of the most significant problems of the modern society is providing the population with food. This issue is currently being considered almost in all countries of the world as an important goal of governmental policy such as rural territories development, sustainable agriculture development, social security, etc. The purpose of the research is to work out scientifically-grounded proposals for effective organization and functioning of modern agrifood market. For that, several methodological approaches have been used: descriptive, analytical, systematic and integrated. As a result, elements of agricultural markets and their relationships were described, the features of agricultural markets development were updated and summarized, methodological principles of their effective organization were formulated and represented. Keywords: agrifood market, sustainable development, market research, governmental policy, food security JEL Classifications: Q10, Q11, Q13.